Adoption of the Mobile Campus in a Cyber University - Han, Insook; Han, Seungyeon (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
The advantages of mobile technologies have not been lost on higher education institutions, and they have tried to provide educational services through the use of mobile learning management system (LMS). However, offering such services does not necessarily mean that the students will adopt the new technology. Thus, the purpose of this study was to examine what factors facilitate and hinder the students’ adoption of the mobile campus. The study was based on the diffusion of innovation model and compared the perceptions of mobile LMS users and nonusers. Eighty-five students in a cyber university responded to the survey, and the results revealed that even though nonusers perceived the advantages of using mobile LMS, they did not adopt the system because of its complexity and resistance. A discussion and the implications for further development of mobile LMS followed.